Local leaders' perception on the adaptive capacity towards climate change impacts among small scale fishermen - Man, Norsida; Saharrudin, Nurul Farhana; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
This study aims to explore the local leaders’ perceptions on the adaptive capacity towards climate change impacts among small scale fishermen. This study is quantitative in nature which used a questionnaire that was developed based on the International Union Conservation of Nature community adaptive capacity framework. Multi-stage cluster sampling was employed resulting in the selection of 300 small scale fishermen from Pengkalan Chepa and Batu Pahat as respondents. Results have shown that local leaders perceived that the small scale fishermen had possessed strong adaptation in three aspects, namely, in terms of the capacity to experiment and learn, community assets and flexibility. A number of discussions have been highlighted in this paper which would hopefully further add understanding on the views of local leaders on adaptive capacity towards climate change impacts among small scale fishermen in Malaysia.